“Architecture is Gesture” : the ornamentation of minbars in selected old mosques of Melaka - Nur Dalilah Dahlan,; Mohd Shahrudin Abd Manan, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The argument of ‘architecture is gesture’ suggests an episteme of artefact that celebrates the narration of human culture. This article explores the ‘gesture’ of mosque architecture. The exploration is conducted with particular reference to the ornamentation of minbar. In the context of Malay art, minbar is considered evidence of traditional ingenuity. The design of minbar reflects the beauty of intricate composition and the skillfulness of craftsmanship. Visits to old mosques as recommended by the Malacca Museums Corporation enable the researchers to select minbars with unique design and carvings. The ornamentation of minbars with reference to three selected old mosques in Melaka, namely, Masjid Peringgit, Masjid Kampung Hulu, and Masjid Kampung Keling are discussed. The discussion highlights the ornamentation of minbars as a response to the cultural convergence in Melaka. The article recommends the study of minbars to be concentrated more on its function as ‘signs’ instead of just a mere ‘aesthetic element’. In this respect, the study of minbars may enrich the holistic meaning of Islamic architecture. It can also be seen as a sign of a harmonious plural society in 18th century Melaka.